2016
DOI: 10.1017/s1474748016000177
|View full text |Cite
|
Sign up to set email alerts
|

Central Limit Theorem for the Modulus of Continuity of Averages of Observables on Transversal Families of Piecewise Expanding Unimodal Maps

Abstract: Abstract. Consider a C 2 family of mixing C 4 piecewise expanding unimodal maps t ∈ [a, b] → ft, with a critical point c, that is transversal to the topological classes of such maps. Given a Lipchitz observable φ consider the functionwhere µt is the unique absolutely continuous invariant probability of ft. Suppose that σt > 0 for every t ∈ [a, b], whereWe show that

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 20 publications
(56 reference statements)
2
19
0
Order By: Relevance
“…We then consider the case when the microscopic dynamics when viewed in isolation does not obey LRT. The simplest such system is the logistic map as established by Baladi and co-workers [8,9,7,10,18]. For concreteness, we consider perturbations of the modified logistic map that was introduced in [50],…”
Section: Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…We then consider the case when the microscopic dynamics when viewed in isolation does not obey LRT. The simplest such system is the logistic map as established by Baladi and co-workers [8,9,7,10,18]. For concreteness, we consider perturbations of the modified logistic map that was introduced in [50],…”
Section: Modelmentioning
confidence: 99%
“…Consider Figure 5. Response term E ε Ψ for an uncoupled heat bath scenario for the map (17) where the parameters are sampled from a raised cosine distribution (18). (a) Infinite M limit with confidence intervals (black) and 21-point moving average with confidence intervals (white) from 15 realisations of 6000 iterates for 10 6 parameters a (j) independently selected for each ε.…”
Section: 23mentioning
confidence: 99%
See 2 more Smart Citations
“…In a separate strand of research mathematicians have tried to obtain rigorous results extending the validity of LRT to deterministic dynamical systems. There was initial success by Ruelle [51,52,53,54] in the case of uniformly hyperbolic Axiom A systems, however the works of Baladi and colleagues undermined hopes that LRT typically holds in dynamical systems [6,7,4,5,15]. They showed that simple dynamical systems such as the logistic map do not obey LRT but rather their invariant measure changes non-smoothly with respect to the perturbation (even considering only chaotic parameter values).…”
Section: Introductionmentioning
confidence: 99%